The Influence of Storage Media, Storage Room, and Time of Storage on Propagules Viability of Rhizophora stylosa Griff - Cecep Kusmana; Muhammad Kalingga F; Dida Syamsuwida (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Indonesia as an archipelagic country has a coastline and partly overgrown with mangrove forest which is the dominant type of coastal areas. However, at present the mangrove forests have been degraded which causes a decrease in forest potency. The effort that can be done to improve the return potential of these mangrove forests is by rehabilitation of mangrove forest. Rhizophora sp., including the type of Rhizophora stylosa Griff., is a pioneer tree species in the mangrove forest which has an important meaning in the mangrove forest etablishment. The main problem of this type of R. Stylosa that is the seed classified into the recalcitrant ones. Therefore, the technique of seed storage is a very important activity to be developed for supporting the success of mangrove rehabilitation activities that have been degraded. The purpose of this study is to discover the influence of storage media, storage room, and time of storage on the propagule viability of R. stylosa, and to compare the R. stylosa propagule germination potential between cutting test and directly propagule germination test results. The research was conducted at the greenhouse and Silviculture Laboratory, Faculty of Forestry IPB and Seed Technology Research Institute Laboratory (BPTP), Bogor.